ANALISIS KEBUTUHAN PENGEMBANGAN MODEL KETELADANAN BERBASIS INTERAKTIF DIGITAL STORYBOOK UNTUK PENANAMAN KESANTUNAN BERBAHASA ANAK USIA DINI - Sopi Masturoh; Purwati; Fauziah Syarifatul Huriyah (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
Language politeness is a crucial aspect in developing the character and social skills of early childhood. However, in practice, various problems remain, such as the influence of an unsupportive environment, limited learning strategies, and suboptimal use of learning media. This study aims to analyze the need to develop a role model based on interactive digital storybooks to instill language politeness in early childhood. This research is part of the analysis and exploration phase of the Educational Design Research (EDR) approach using qualitative descriptive methods. The study was conducted at TK Fatinah, involving one principal and one teacher as research subjects. Data were collected through semi-structured interviews and then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the family, school, and peer environments influence children's language politeness; habituation through role modeling is the primary strategy; the use of learning media is still limited; and there is a need to develop interactive digital storybooks that integrate role modeling into learning. These findings form the basis for developing an innovative learning model to support language politeness in early childhood.